KEPENTINGAN INDONESIA TERHADAP JEPANG DALAM PROYEK KERETA CEPAT JAKARTA-SURABAYA - Ramadhani, Dinda; Prasodjo, Haryo; Rijal, Najamuddin; Rosyida, Hamdan (Dauliyah: Journal of Islam and International Affairs, 2022)
The high-speed train infrastructure project is not only seen as an economic issue, more than that, high-speed train technology has developed into a world political issue. Rivalry between countries and manufacturers of high-speed trains occurs in several regions of the world, one of which is Indonesia. The rivalry between China and Japan in the high-speed train provides an opportunity for Indonesia to play a role and maximize bargaining power to take advantage of the rivalry. Japan, which is Indonesia's strategic partner, received the opportunity to build the Jakarta-Surabaya high-speed train after previously losing to China in the Jakarta-Bandung high-speed rail project. Using an international political economy approach, this paper will discuss the shape of Indonesia's interest in Japan in the Jakarta-Surabaya high-speed rail construction project. There are several things that are seen, namely Japan's strategic role for Indonesia in terms of investment, Japan's important role for Indonesia's economic growth, Indonesia's need for sustainable infrastructure development and regional connectivity, and the need for technology transfer aimed at building human resources and realizing the better transportation system.